INDIRECT METHODS OF MEASURING FLОW RATE AND PRESSURE DROP OF ROTARY BLOOD PUMPS - G. P. Itkin; I. A. Filatov; K. N. Dozorov; A. V. Adaskin (Вестник трансплантологии и искусственных органов)
The article describes complex software to calculate the main parameters of the axial pump (pressure drop and flow rate) on the basis of an analysis of its technical characteristics (current consumption and pump speed). It is shown that the calculated value of pressure drop and flow rate throughout the range of operating loads and pump speeds is different from the measured one by no more than 10%. It is shown that this software package may be included in the control system of axial pump.